2010
DOI: 10.1128/aac.01354-09
|View full text |Cite
|
Sign up to set email alerts
|

Early Bactericidal Activity and Pharmacokinetics of PA-824 in Smear-Positive Tuberculosis Patients

Abstract: PA-824 is a novel nitroimidazo-oxazine being evaluated for its potential to improve tuberculosis (TB) therapy. This randomized study evaluated safety, tolerability, pharmacokinetics, and extended early bactericidal activity of PA-824 in drug-sensitive, sputum smear-positive, adult pulmonary tuberculosis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
110
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(123 citation statements)
references
References 20 publications
12
110
0
1
Order By: Relevance
“…In the monotherapy trials, a daily dose of 50 mg had lower bactericidal activity than higher doses, but there was no significant difference in bactericidal activity of daily doses from 100 to 1200 mg. The NC-001 trial demonstrated excellent bactericidal activity in the PaMZ combination at a daily dose of 200 mg [77,78]. An 8-week phase IIb serial sputum colony counting trial demonstrated a greater time-dependent decline of viable bacteria in subjects with drug-sensitive pulmonary TB at 8 weeks (71.4% negative in liquid culture in comparison with only 37.8% of subjects treated with the standard HRZE control; p<0.05) [7].…”
Section: The Stand Trialmentioning
confidence: 99%
“…In the monotherapy trials, a daily dose of 50 mg had lower bactericidal activity than higher doses, but there was no significant difference in bactericidal activity of daily doses from 100 to 1200 mg. The NC-001 trial demonstrated excellent bactericidal activity in the PaMZ combination at a daily dose of 200 mg [77,78]. An 8-week phase IIb serial sputum colony counting trial demonstrated a greater time-dependent decline of viable bacteria in subjects with drug-sensitive pulmonary TB at 8 weeks (71.4% negative in liquid culture in comparison with only 37.8% of subjects treated with the standard HRZE control; p<0.05) [7].…”
Section: The Stand Trialmentioning
confidence: 99%
“…For tuberculosis, lack of a reliable biomarker of treatment response makes it difficult to define PK-PD relationships. PA-824 is being tested in a 2-month phase 2B treatment trial at doses of 100 mg and 200 mg daily because doses from 100 mg to 1,000 mg had similar activities in the 2-week dose-ranging phase 2A monotherapy studies; only at 50 mg daily was early bactericidal activity (EBA) decreased (33,34). Preclinical studies suggest time-dependent activity of PA-824 against M. tuberculosis (35), suggesting that the AUC 0 -24 may be a key pharmacodynamic parameter; however, target AUC values have not been defined.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, PA-824 has been well tolerated with constant pharmacodynamic parameters when given once daily, with the maximum serum drug level reached about 4-5 h following oral administration [59,67,68].…”
Section: Pa-824 ( Pretomanid)mentioning
confidence: 99%